Concept mapping: a process to promote staff learning and problem-solving in residential dementia care. - Aberdeen SM; Leggat SG; Barraclough S (Dementia (14713012), 2010)
A person-centred assessment and problem-solving approach is acknowledged widely as the preferred method for managing the behavioural and psychological symptoms of residents with dementia (BPSD). Currently this is not well implemented in residential dementia care. In this paper concept mapping is discussed critically as a process that has the potential to improve the quality of resident care by providing an efficient framework for problem-solving. It facilitates data analysis, a missing link in problem-solving BPSD. Overtime concept mapping may also reduce the burden on individual staff, improve the skills and knowledge of all levels of staff and foster learning organizations. Potential challenges to the implementation and success of the process, which include staff shortages, the need for effective leadership and organizational support, are also addressed.